lncRNA NORAD modulates STAT3/STAT1 balance and innate immune responses in human cells via interaction with STAT3 - Amir Argoetti; Dor Shalev; Galia Polyak; Noa Shima; Hadas Biran; Tamar Lahav; Tamar Hashimshony; Yael Mandel-Gutfreund (Nature Communications)
Abstract Long non-coding RNAs (lncRNAs) are pivotal regulators of cellular processes. Here we reveal an interaction between the lncRNA NORAD, noted for its role in DNA stability, and the immune related transcription factor STAT3 in embryonic and differentiated human cells. Results from NORAD knockdown experiments implicate NORAD in facilitating STAT3 nuclear localization and suppressing antiviral gene activation. In NORAD-deficient cells, STAT3 remains cytoplasmic, allowing STAT1 to enhance antiviral activity. Analysis of RNA expression data from in vitro experiments and clinical samples demonstrates reduced NORAD upon viral infection. Additionally, evolutionary conservation analysis suggests that this regulatory function of NORAD is restricted to humans, potentially owing to the introduction of an Alu element in hominoids. Our findings thus suggest that NORAD functions as a modulator of STAT3-mediated immune suppression, adding to the understanding of lncRNAs in immune regulation and evolutionary adaptation in host defense mechanisms.